Patient-reported outcomes from the MIRASOL trial evaluating mirvetuximab soravtansine versus chemotherapy in patients with folate receptor α-positive, platinum-resistant ovarian cancer: a randomised, open-label, phase 3 trial - Van Gorp, Toon; Moore, Kathleen N; Konecny, Gottfried E; Leary, Alexandra; García-García, Yolanda; Banerjee, Susana; Lorusso, Domenica; Lee, Jung-Yun; Moroney, John W; Caruso, Giuseppe; Klasa-Mazurkiewicz, Dagmara; Tromp, Jacqueline; et al. (The Lancet. Oncology, 2025)
BACKGROUND: Mirvetuximab soravtansine-gynx (MIRV) is a first-in-class antibody-drug conjugate targeting folate receptor α (FRα), approved by the US Food and Drug Administration for the treatment of platinum-resistant ovarian cancer in the USA. Here, we report patient-reported outcomes for participants treated with MIRV compared with investigator's choice of chemotherapy from the phase 3 MIRASOL trial, which met its primary endpoint of progression-free survival and key secondary endpoints of objective response rate and overall survival. METHODS: The MIRASOL trial was a confirmatory, phase 3, randomised, controlled, open-label trial, building on the phase 2 SORAYA trial which had previously demonstrated the safety and efficacy of MIRV in platinum-resistant ovarian cancer. Patients 18 years or older with a confirmed platinum-resistant, recurrent high-grade serous epithelial ovarian cancer diagnosis were recruited from 253 sites including hospitals, academic centres, and community centres in 21 countries. Patients must have received one to three previous systemic anticancer therapies, and have high FRα tumour expression (≥75% tumour cells with an immunohistochemistry score of ≥2+ membrane staining using the PS2+ scoring method), one or more lesions with measurable disease, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (1:1) to MIRV or investigator's choice of chemotherapy, stratified by number of previous therapy lines and the type of investigator's choice of chemotherapy. Therapies were administered in an open-label manner; MIRV was administered intravenously at 6 mg/kg of adjusted ideal bodyweight every 3 weeks. The primary endpoint was progression-free survival. Key secondary endpoints were objective response rate, overall survival, and a 15·0-point or greater improvement at week 8 or 9 in abdominal and gastrointestinal symptoms using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Ovarian Cancer Module (EORTC QLQ-OV28) in the intention-to-treat population. The MIRASOL trial was registered at ClinicalTrials.gov (NCT04209855), the Gynecologic Oncology Group (GOG 3045), and the European Network of Gynaecological Oncological Trial Groups (ENGOT-ov55), and is complete. FINDINGS: Between Feb 3, 2020, and Aug 3, 2022, 453 patients were enrolled and randomly assigned to treatment (227 to the MIRV group and 226 to the investigator's choice of chemotherapy group). All patients were female; 301 (66%) participants were White, 53 (12%) were Asian, 13 (3%) were Black, and 86 (19%) were of another race or not reported; 27 (6%) were Hispanic or Latino. The median follow-up for the study, determined by the reverse Kaplan-Meier method, was 13·1 months (95% CI 12·1-14). QLQ-OV28 completion rates were 86% (365 of 425) at baseline and 81% (282 of 349) at week 8 or 9. 34 (21·0%; 95% CI 15·0-28·1) of 162 patients treated with MIRV reported improvement in QLQ-OV28 abdominal and gastrointestinal scores, compared with 23 (15·3%; 10·0-22·1) of 150 patients treated with the investigator's choice of chemotherapy. These differences were not statistically significant (odds ratio 1·5 [95% CI 0·8-2·6]; p=0·26). INTERPRETATION: MIRV did not seem to impair or improve patient quality of life compared with investigator's choice of chemotherapy. The similar quality-of-life outcomes in the two treatment groups, combined with the previously reported higher efficacy of MIRV compared with single-agent chemotherapy, support MIRV as new treatment option for FRα-positive platinum-resistant ovarian cancer. FUNDING: AbbVie.
Keywords: senioři; epiteliální ovariální karcinom; Maytansine; maytansin; lidé; doba přežití bez progrese choroby; Middle Aged; Folate Receptor 1; nádory vaječníků; Patient Reported Outcome Measures; Adult; chemorezistence; ženské pohlaví; Humans; Drug Resistance, Neoplasm; hodnocení výsledků péče pacientem; Antibodies, Monoclonal, Humanized; Progression-Free Survival; lidé středního věku; Immunoconjugates; folátový receptor 1; Antineoplastic Combined Chemotherapy Protocols; Carcinoma, Ovarian Epithelial; protokoly protinádorové kombinované chemoterapie; dospělí; imunokonjugáty; Female; Ovarian Neoplasms; Aged; humanizované monoklonální protilátky